Electrode material of three-dimensional heterojunction supercapacitor and preparation method thereof
By in-situ synthesis of (NiCo)xSy on NiCo-LDH nanosheets to form a three-dimensional heterojunction NiCo-LDH@(NiCo)xSy structure, the problem of low energy density of existing supercapacitor electrode materials is solved, and the electrochemical performance and stability are significantly improved.
Patent Information
- Application Number
- CN202510053931.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-25
AI Technical Summary
The electrode materials of existing supercapacitors have low energy density and are difficult to meet high power requirements due to blocked ion diffusion channels and poor redox activity.
The electrode material of a three-dimensional heterojunction supercapacitor is used to synthesize (NiCo)xSy in situ on NiCo-LDH nanosheets to form a three-dimensional heterojunction NiCo-LDH@(NiCo)xSy structure, which increases the electrochemical capacity, accelerates the electron transfer speed, improves electrochemical activity, and reduces the decrease ratio of the capacity ratio initial value in the GCD cycle.
The electrochemical properties of the electrode materials are significantly improved, the electrochemical activity and electrochemical stability are enhanced, the cycle life is extended, and the initial reduction ratio of capacity is reduced.
Smart Images

Figure CN119889937A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of supercapacitor electrode materials, and in particular relates to an electrode material for a three-dimensional heterojunction supercapacitor and a preparation method thereof. Background Art
[0002] Supercapacitors have attracted widespread attention in many fields due to their high power density, excellent cycle performance, and fast charge and discharge capabilities. With the accelerated development of portable, wearable electronic products and artificial intelligence, the demand for equipping these electronic products with competitive energy supply equipment is increasing day by day, which is bound to put forward higher energy storage and stability requirements for supercapacitors as new energy storage power devices. However, supercapacitors are currently limited by blocked ion diffusion channels and poor redox activity of electrode materials, resulting in low energy density. Therefore, by constructing electrode materials with continuous conductive porous networks, high specific surface area and pseudocapacitive behavior, and superior interfacial electronic conductivity, it is beneficial to accelerate transfer / diffusion kinetics and Faraday storage, which is crucial to the realization of high energy density of supercapacitors.
[0003] Nickel cobalt hydroxide (NiCo-LDH) electrode materials are widely used in supercapacitors due to their rich and flexible structure, variable valence state and high conductivity. However, single NiCo-LDH is limited by its low specific capacity, poor rate performance and short cycle life, which makes it difficult to meet high power requirements, so it needs to be modified to improve its electrochemical performance.
[0004] Researchers have adopted strategies such as nano-morphology control, doping and composite with carbon materials to improve its capacity. Among bimetallic compounds, sulfur has a lower electronegativity than oxygen, and nickel cobalt sulfide (NiCo) x S y ) has the advantages of smaller band gap energy, higher conductivity and stronger charge storage capacity, and can be used as a new type of battery-type material in supercapacitors. The composition / structure design of electrode materials is crucial to maintain the ideal electrochemical performance in assembled supercapacitor devices. Therefore, how to design a supercapacitor based on NiCo-LDH and (NiCo) x S y The key is to cleverly design the composition and structure of electrode materials. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and provide an electrode material for a three-dimensional heterojunction supercapacitor and a preparation method thereof.
[0006] In order to achieve the purpose of the present invention, the present invention is implemented by adopting the following technical solutions.
[0007] The electrode material of a three-dimensional heterojunction supercapacitor is composed of a substrate two-dimensional nanosheet NiCo-LDH and (NiCo) synthesized in situ on the NiCo-LDH nanosheet. x S y The formed three-dimensional heterojunction NiCo-LDH@(Ni Co) x S y The three-dimensional heterojunction NiCo-LDH@(NiCo) x S y It is a hollow nano flower ball with pore space; the three-dimensional heterojunction NiCo-LDH@(NiCo) x S y It can increase the electrochemical capacity, accelerate the electron transfer rate, improve the electrochemical activity, and reduce the decrease ratio of the capacity to the initial value in the GCD cycle.
[0008] A three-dimensional heterojunction NiCo-LDH@(NiCo) x S y The preparation method is to prepare NiCo-LDH into a solution, add a sulfur source to the NiCo-LDH solution for an in-situ synthesis reaction, and after the reaction is completed, wash with ethanol and dry at 50-70°C to obtain a three-dimensional heterojunction NiCo-LDH@(NiCo) x S y ; Wherein: the reaction temperature of the in-situ synthesis reaction is 120-140°C and the time is 1-6h.
[0009] As a preferred embodiment of the present invention, the mass ratio of the NiCo-LDH to the sulfur source is 1:1-1:3.
[0010] As a preferred embodiment of the present invention, the sulfur source is at least one of sodium sulfide, thioacetamide and thiourea.
[0011] As a preferred embodiment of the present invention, the preparation method of NiCo-LDH comprises the following steps:
[0012] S51, dissolving Co(NO3)2·6H2O in a mixed solution of isopropanol and glycerol, subjecting the prepared reaction solution to a hydrothermal reaction at a reaction temperature of 160-180°C and a heat preservation time of 6-8h; after the reaction is complete, washing by centrifugation with ethanol, and then drying at 50-70°C to obtain cobalt glycerate;
[0013] S52. Co-glycerate and Ni(NO3)2·6H2O are respectively prepared into solutions, the two solutions are mixed, and then the solutions are subjected to a hydrothermal reaction at a reaction temperature of 140-160°C for 2-5 hours, and then washed with ethanol and dried at 50-70°C to obtain NiCo-LDH.
[0014] As a preferred embodiment of the present invention, the Co(NO3)2·6H2O in step S51 is 0.2-1 mmol, the volume of isopropanol is 20-50 mL, and the volume of glycerol is 5-10 mL.
[0015] As a preferred embodiment of the present invention, the co-glycerate solution is prepared by ultrasonically dispersing 10-20 mg co-glycerate in 6-10 mL ethanol; wherein: the ultrasonic dispersion is to ultrasonically disperse the co-glycerate in ethanol for 5 to 10 minutes.
[0016] As a preferred embodiment of the present invention, the Ni(NO3)2·6H2O solution is prepared by dissolving 100-200 mg Ni(NO3)2·6H2O in 4-10 mL deionized water.
[0017] Beneficial Effects
[0018] (1) The electrode material in the present invention is a three-dimensional heterojunction nanoflower structure, which is synthesized in situ on NiCo-LDH nanosheets (NiCo) x S y , with a more stable crystal structure and stronger conductivity, which can reveal more active sites and improve charge transfer ability;
[0019] (2) The heterogeneous interface composed of two components in the present invention can rearrange the crystal structure and electric field distribution of the active material, increase the electronic state density near the Fermi level and reduce the adsorption energy, thereby promoting OH - The adsorption and protonation / deprotonation reactions of the electrode materials can be enhanced, thereby enhancing the intrinsic activity and electrochemical stability of the electrode materials.
[0020] (3) The raw materials used in the present invention are cheap and easily available, and the synthesis process is simple and easy to control, which is suitable for industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 NiS2 prepared in Comparative Example 1, NiCo-LDH prepared in Comparative Example 2, and NiCo-LDH@(NiCo) prepared in Example 1 x S y XRD pattern of
[0022] Figure 2NiS2 prepared in Comparative Example 1, NiCo-LDH prepared in Comparative Example 2, and NiCo-LDH@(NiCo) prepared in Example 1 x S y SEM images; among them, Figures a and b are SEM images of NiS2, Figures c and d are SEM images of NiCo-LDH, and Figures e and f are SEM images of NiCo-LDH@(NiCo) x S y SEM images of
[0023] Figure 3 NiCo-LDH@(NiCo) x S y High-resolution TEM image of electrode materials;
[0024] Figure 4 NiCo-LDH@(NiCo) x S y XPS graph of
[0025] Figure 5 NiS2 prepared in Comparative Example 1, NiCo-LDH prepared in Comparative Example 2, and NiCo-LDH@(NiCo) prepared in Example 1 x S y At a scan rate of 20 mV s -1 Cyclic voltammetry (CV) diagram and current density of 1A g -1 GCD diagram of
[0026] Figure 6 NiS2 prepared in Comparative Example 1, NiCo-LDH prepared in Comparative Example 2, and NiCo-LDH@(NiCo) prepared in Example 1 x S y The functional relationship between the peak oxidation current and the square root of the scan rate;
[0027] Figure 7 NiCo-LDH@(NiCo) prepared in Example 1 x S y At a current density of 5A -1 The following is the performance curve of 6000 cycles. DETAILED DESCRIPTION
[0028] The present invention will be further described with reference to the accompanying drawings and embodiments.
[0029] As embodiment 1 of the present invention, a method for preparing a three-dimensional heterojunction supercapacitor electrode material comprises the following steps:
[0030] Step 1: 0.38mmol Co(NO3)2·6H2O was dissolved in 40mL isopropanol, and 8mL glycerol was added to the solution and stirred at room temperature for 30min. After stirring, the prepared reaction solution was subjected to hydrothermal reaction at 180℃ for 6h. After the reaction was complete, it was washed by centrifugation with ethanol 3 times and dried at 60℃ for 12h to obtain Co-glycerate.
[0031] Step 2: 11 mg Co-glycerate was ultrasonically dispersed in 6 mL ethanol to form solution A; 150 mg Ni(NO3)2·6H2O was dissolved in 4 mL deionized water to form solution B. After adding solution B to solution A, stirring was continued for 20 min. After stirring, the solution was subjected to hydrothermal reaction at 150 °C for 5 h. After the reaction was complete, it was washed with ethanol by centrifugation 3 times and dried at 60 °C for 12 h to obtain NiCo-LDH.
[0032] Step 3: 50 mg of thioacetamide (TAA) was dissolved in 30 mL of ethanol, and 30 mg of NiCo-LDH was added thereto and stirred for 30 min. After stirring, the solution was subjected to a hydrothermal reaction at 120 °C for 1 h. After the reaction was complete, the solution was washed with ethanol by centrifugation for 3 times and dried at 60 °C for 12 h to obtain NiCo-LDH@(NiCo) x S y .
[0033] As embodiment 2 of the present invention, a method for preparing a three-dimensional heterojunction supercapacitor electrode material comprises the following steps:
[0034] Step 1: 0.4mmol Co(NO3)2·6H2O was dissolved in 20mL isopropanol, and 5mL glycerol was added to the solution and stirred at room temperature for 30min. After stirring, the prepared reaction solution was subjected to hydrothermal reaction at 160℃ for 6h. After the reaction was complete, it was washed by centrifugation with ethanol 3 times and dried at 60℃ for 12h to obtain Co-glycerate.
[0035] Step 2: 10 mg Co-glycerate was ultrasonically dispersed in 6 mL ethanol to form solution A; 100 mg Ni(NO3)2·6H2O was dissolved in 5 mL deionized water to form solution B. After adding solution B to solution A, stirring was continued for 20 min. After stirring, the solution was subjected to hydrothermal reaction at 140 °C for 5 h. After the reaction was complete, it was washed by centrifugation with ethanol 3 times and dried at 60 °C for 12 h to obtain NiCo-LDH.
[0036] Step 3: 30 mg TAA was dissolved in 30 mL ethanol, 30 mg NiCo-LDH was added, and stirring continued for 30 min. After stirring, the solution was subjected to hydrothermal reaction at 120 °C for 1 h. After the reaction was complete, it was washed by centrifugation with ethanol for 3 times and dried at 60 °C for 12 h to obtain NiCo-LDH@(NiCo) x S y .
[0037] As embodiment 3 of the present invention, a method for preparing a three-dimensional heterojunction supercapacitor electrode material comprises the following steps:
[0038] Step 1: 0.6mmol Co(NO3)2·6H2O was dissolved in 35mL isopropanol, and 6mL glycerol was added to the solution and stirred at room temperature for 30min. After stirring, the prepared reaction solution was subjected to hydrothermal reaction at 160℃ for 10h. After the reaction was complete, the solution was washed by centrifugation with ethanol for 3 times and dried at 60℃ to obtain Co-glycerate.
[0039] Step 2: 15 mg Co-glycerate was ultrasonically dispersed in 8 mL ethanol to form solution A; 120 mg Ni(NO3)2·6H2O was dissolved in 8 mL deionized water to form solution B. After adding solution B to solution A, stirring was continued for 20 min. After stirring, the solution was subjected to hydrothermal reaction at 150 ° C for 4 h. After the reaction was complete, it was centrifuged and washed 3 times with ethanol and dried at 60 ° C to obtain NiCo-LDH.
[0040] Step 3: 40 mg TAA was dissolved in 30 mL ethanol, 30 mg NiCo-LDH was added, and stirring continued for 30 min. After stirring, the solution was subjected to hydrothermal reaction at 120 °C for 6 h. After the reaction was complete, it was washed by centrifugation with ethanol for 3 times and dried at 60 °C to obtain NiCo-LDH@(NiCo) x S y .
[0041] As embodiment 4 of the present invention, a method for preparing a three-dimensional heterojunction supercapacitor electrode material comprises the following steps:
[0042] Step 1: 0.4mmol Co(NO3)2·6H2O was dissolved in 40mL isopropanol, and 8mL glycerol was added to the solution and stirred at room temperature for 30min. After stirring, the prepared reaction solution was subjected to hydrothermal reaction at 180℃ for 8h. After the reaction was complete, it was washed by centrifugation with ethanol 3 times and dried at 60℃ to obtain Co-glycerate.
[0043] Step 2: 18 mg Co-glycerate was ultrasonically dispersed in 10 mL ethanol to form solution A; 140 mg Ni(NO3)2·6H2O was dissolved in 8 mL deionized water to form solution B. After adding solution B to solution A, stirring was continued for 20 min. After stirring, the solution was subjected to hydrothermal reaction at 160 ° C for 6 h. After the reaction was complete, it was centrifuged and washed 3 times with ethanol and dried at 60 ° C to obtain NiCo-LDH.
[0044] Step 3: 60 mg TAA was dissolved in 30 mL ethanol, 15 mg NiCo-LDH was added, and stirring continued for 30 min. After stirring, the solution was subjected to hydrothermal reaction at 140 °C for 6 h. After the reaction was complete, it was washed by centrifugation with ethanol for 3 times and dried at 60 °C to obtain NiCo-LDH@(NiCo) x S y .
[0045] As Comparative Example 1 of the present invention, the NiS2 electrode preparation process is as follows:
[0046] Step 1: 0.38mmol Co(NO3)2·6H2O was dissolved in 40mL isopropanol, and 8mL glycerol was added to the solution and stirred at room temperature for 30min. After stirring, the prepared reaction solution was subjected to hydrothermal reaction at 180℃ for 6h. After the reaction was complete, it was washed by centrifugation with ethanol 3 times and dried at 60℃ for 12h to obtain Co-glycerate.
[0047] Step 2: 11 mg Co-glycerate was ultrasonically dispersed in 6 mL ethanol to form solution A; 150 mg Ni(NO3)2·6H2O was dissolved in 4 mL deionized water to form solution B. After adding solution B to solution A, stirring was continued for 20 min. After stirring, the solution was subjected to hydrothermal reaction at 150 °C for 5 h. After the reaction was complete, it was washed with ethanol by centrifugation 3 times and dried at 60 °C for 12 h to obtain NiCo-LDH.
[0048] Step 3: 50 mg TAA was dissolved in 30 mL ethanol, 30 mg NiCo-LDH was added, and stirring continued for 30 min. After stirring, the solution was subjected to hydrothermal reaction at 120 ° C for 6 h. After the reaction was complete, it was washed by centrifugation with ethanol for 3 times and dried at 60 ° C for 12 h to obtain NiS2.
[0049] As comparative example 2 of the present invention, the NiCo-LDH electrode preparation process is as follows:
[0050] Step 1: 0.4mmol Co(NO3)2·6H2O was dissolved in 40mL isopropanol, and 8mL glycerol was added to the solution and stirred at room temperature for 30min. After stirring, the prepared reaction solution was subjected to hydrothermal reaction at 180℃ for 6h. After the reaction was complete, the solution was washed by centrifugation with ethanol for 3 times and dried at 60℃ to obtain Co-glycerate.
[0051] Step 2: 12 mg Co-glycerate was ultrasonically dispersed in 6 mL ethanol to form solution A; 150 mg Ni(NO3)2·6H2O was dissolved in 4 mL deionized water to form solution B. After adding solution B to solution A, stirring was continued for 20 min. After stirring, the solution was subjected to hydrothermal reaction at 150 °C for 5 h. After the reaction was complete, it was washed with ethanol by centrifugation 3 times and dried at 60 °C to obtain NiCo-LDH.
[0052] NiS2 prepared in Comparative Example 1, NiCo-LDH prepared in Comparative Example 2, and NiCo-LDH@(NiCo) prepared in Example 1 x S y Structural characterization analysis:
[0053] NiS2 prepared in Comparative Example 1, NiCo-LDH prepared in Comparative Example 2, and NiCo-LDH@(NiCo) prepared in Example 1 x S y The diffraction peaks at 27.2°, 31.9°, 35.3°, 38.7°, 45.3°, 53.9°, 59.0° and 61.5° correspond to the (111), (200), (210), (211), (220), (311), (230) and (321) crystal planes of NiS2 (JCPDS No.11-0099), respectively. Seven diffraction peaks appeared at 11.2°, 22.5°, 34.7°, 38.8°, 46.1°, 60.4° and 61.5°, corresponding to the (003), (006), (012), (015), (018), (110) and (113) crystal planes of NiCo-LDH (JCPDS No. 40-0216) respectively; NiCo-LDH was subjected to sulfurization treatment, and it was found that the XRD patterns before and after sulfurization showed the same diffraction peak positions. The difference is that the intensity of each diffraction peak of the sulfurized product is weaker than that of NiCo-LDH, indicating that the sulfurization reaction only occurs on the surface of NiCo-LDH and does not destroy its internal structure, confirming the heterogeneous structure of NiCo-LDH@(NiCo) x S y The formation of Figure 1 shown.
[0054] NiCo-LDH is a nanoflower ball assembled from interlaced nanosheets, and the interior is a hollow structure, such as Figure 2 As shown in Figures c and d; after further sulfurization treatment, NiCo-LDH@(NiCo) x S y The shape of the flower ball is still maintained, and the outer nanosheet structure is retained, further enhancing the conductivity of the material. Figure 2 As shown in Figures e and f in Figure 1, NiS2 shows uneven particle sizes and obvious agglomeration, and the flake-like flower ball morphology disappears, as shown in Figure 2. Figure 2 As shown in Figure a and Figure b.
[0055] from Figure 3 In (a), we can see NiCo-LDH@(NiCo) x S y It still presents a three-dimensional nanoflower ball composed of nanosheets, and the inner core hollow ball has obvious pore space. Figure 3 (b) shows NiCo-LDH@(NiCo) x S y From the HRTEM image, it can be observed that the lattice fringes at 0.23 nm correspond to the (015) crystal plane of the NiCo-LDH crystal; while the surrounding area of NiCo-LDH exhibits amorphous characteristics, which means that the amorphous (NiCo) x S y Covered around the NiCo-LDH crystals, they are adjacent to each other with clear boundaries, indicating that NiCo-LDH@(NiCo) x S y formation. Figure 3 The built-in image in (b) is the SAED image, and a weak diffraction halo is observed, which means that the prepared NiCo-LDH@(NiCo) x S y The overall crystallinity is relatively poor.
[0056] like Figure 4 As shown, NiCo-LDH@(NiCo) prepared in Example 1 x S y The electrode material contains Co, Ni, S and O elements at the same time.
[0057] NiS2 prepared in Comparative Example 1, NiCo-LDH prepared in Comparative Example 2, and NiCo-LDH@(NiCo) prepared in Example 1 x S y Performance test:
[0058] Electrochemical performance tests were conducted on a CHI 760E electrochemical workstation and a blue battery test system. The working electrode was prepared by coating method, and the process was as follows: first, the weight of the dry nickel foam was accurately weighed, and then the prepared electrode, acetylene black and polytetrafluoroethylene were mixed in a mass ratio of 8:1.5:0.5, and an appropriate amount of water was added to grind into a uniform slurry, which was coated on the weighed nickel foam. The coating area was approximately 1×1 cm square, and then dried in a 60°C drying oven for 12 h.
[0059] from Figure 5 As shown in Figure (a), the three groups of materials all have two pairs of obvious redox peaks in the voltage range of 0 to 0.6 V, indicating that these electrode materials are battery-type behavior materials. Among them, NiCo-LDH@(NiCo) prepared in Example 1 x S y The peak current and area of the curve increased significantly, indicating that the multi-component product after sulfurization has an increased electrochemical capacity. Figure 5 Figure (b) reveals the NiCo-LDH@(NiCo) prepared in Example 1 x S y The longer charge and discharge time is consistent with the observation results of the CV curve, which may be due to the interaction between NiCo-LD H and (NiCo) x S y The heterogeneous structures and components expose more active sites and accelerate electron transfer.
[0060] NiCo-LDH@(NiCo) x S y The straight line fitted by the electrode has a large slope and current response, indicating that the electrode has good electrochemical activity, such as Figure 6 shown.
[0061] NiCo-LDH@(NiCo) x S y After 6000 GCD cycles, the capacity of the electrode decreased by 14% compared with the initial value. Figure 7 shown.
[0062] Table 1 compares the performance of the materials of the present invention with other reported transition metal sulfides, indicating that the NiCo-LDH@(NiCo) prepared by the present invention is x S y It has higher electrochemical performance.
[0063] Table 1 NiCo-LDH@(NiCo) x S y Comparison with other reported transition metal sulfides
[0064]
[0065] The preferred embodiments of the present invention are described above with reference to the accompanying drawings, but the scope of the rights of the present invention is not limited thereto. Any modification, equivalent substitution and improvement made by a person skilled in the art without departing from the scope and essence of the present invention should be within the scope of the rights of the present invention.
Claims
1. An electrode material for a three-dimensional heterojunction supercapacitor, characterized in that: The electrode material is composed of a substrate two-dimensional nanosheet NiCo-LDH and (NiCo) synthesized in situ on the NiCo-LDH nanosheet. x S y The formed three-dimensional heterojunction NiCo-LDH@(NiCo) x S y The three-dimensional heterojunction NiCo-LDH@(NiCo) x S y It is a hollow nano flower ball with pore space; the three-dimensional heterojunction NiCo-LDH@(NiCo) x S y It can increase the electrochemical capacity, accelerate the electron transfer speed, improve the electrochemical activity, and reduce the decrease ratio of the capacity to the initial value in the constant current charge and discharge curve (GCD) cycle.
2. A three-dimensional heterojunction NiCo-LDH@(NiCo) x S y The preparation method is characterized in that: The preparation method is to prepare NiCo-LDH into a solution, add a sulfur source to the NiCo-LDH solution to carry out an in-situ synthesis reaction, and after the in-situ synthesis reaction is completed, wash with ethanol and dry at 50-70°C to obtain a three-dimensional heterojunction NiCo-LDH@(NiCo) x S y ; Wherein: the temperature of the in-situ synthesis reaction is 120-140°C and the time is 1-6h.
3. A three-dimensional heterojunction NiCo-LDH@(NiCo) according to claim 2 x S y The preparation method is characterized in that: The mass ratio of the NiCo-LDH to the sulfur source is 1:1-1:
3.
4. A three-dimensional heterojunction NiCo-LDH@(NiCo) according to claim 2 or 3 x S y The preparation method is characterized in that: The sulfur source is at least one of sodium sulfide, thioacetamide and thiourea.
5. A three-dimensional heterojunction NiCo-LDH@(NiCo) according to claim 2 x S y The preparation method is characterized in that: The preparation method of NiCo-LDH comprises the following steps: S51, dissolving Co(NO3)2·6H2O in a mixed solution of isopropanol and glycerol, subjecting the prepared reaction solution to a hydrothermal reaction at a reaction temperature of 160-180°C and a heat preservation time of 6-8h; after the reaction is complete, washing by centrifugation with ethanol, and then drying at 50-70°C to obtain cobalt glycerate; S52. Co-glycerate and Ni(NO3)2·6H2O are respectively prepared into solutions, the two solutions are mixed, and then the solutions are subjected to a hydrothermal reaction at a reaction temperature of 140-160°C for 2-5 hours, and then washed with ethanol and dried at 50-70°C to obtain NiCo-LDH.
6. A three-dimensional heterojunction NiCo-LDH@(NiCo) according to claim 5 x S y The preparation method is characterized in that: In the step S51, the amount of Co(NO3)2·6H2O is 0.2-1 mmol, the volume of isopropanol is 20-50 mL, and the volume of glycerol is 5-10 mL.
7. A three-dimensional heterojunction NiCo-LDH@(NiCo) according to claim 5 x S y The preparation method is characterized in that: The co-glycerate solution is prepared by ultrasonically dispersing 10-20 mg co-glycerate in 6-10 mL ethanol; wherein the ultrasonic dispersion is to ultrasonically disperse the co-glycerate in ethanol for 5 to 10 minutes.
8. A three-dimensional heterojunction NiCo-LDH@(NiCo) according to claim 5 x S y The preparation method is characterized in that: The Ni(NO3)2·6H2O solution is prepared by dissolving 100-200 mg Ni(NO3)2·6H2O in 4-10 mL deionized water.
Citation Information
Patent Citations
Sulfurized Ni-Co-Al LDH electrode composite materials and preparation method thereof
CN109119252A
Preparation method of NiCo2S4-coated NiCo-LDH / NF electrode material for photo-assisted supercapacitor
CN117393334A
Preparation method of sulfur atom substituted NiCo LDH nano array material for large-current oxygen evolution
CN117766782A
Preparation method of heteroatom sulfur modified etching enhanced nickel-cobalt double hydroxide electrode material
CN118629800A
NiCo-LDH / Ni (OH) 2 heterojunction composite material, electrode, supercapacitor and preparation method
CN119069268A